(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In this article I.A. Bunin’s work «Smaragd» is considered in the systematic plan. The main aim is the identification of the content and formal signs in the gist of the epic work by I. Bunin. Thus the special attention is paid to the problem of the unreal image at all four analysis stages of the epic work by the principle of isomorphism. Isomorphism is adequate to the natural link of «chaos» and «order» in correlation of the content and the form of the studied categories in the system of the Bunin’s text. The unreal character of the image revealed at the first stage is systemically confirmed at the second stage through the conflict of the personality, then, it will be corrected at the third stage revealing its features at the fourth. As a result, for comprehension of the writer’s intention along with the required signs of character the image, the genre form, the genre version are concretized, the subject, idea, specific features and the style of Bunin’s work are revealed.